2015
DOI: 10.1007/s12519-015-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

New technologies as a strategy to decrease medication errors: how do they affect adults and children differently?

Abstract: Implementation of CPOE programs for pediatrics, communication improvement between healthcare professionals taking care of admitted children and the knowledge of these programs should be the mayor priorities for the safety of hospitalized children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 56 publications
0
19
0
1
Order By: Relevance
“…Further path analysis showed that hardware might affect nurses and thereby indirectly influence the medication safety behaviour of nurses. The study found that information technology might reduce errors; although electronic medical records, electronic prescriptions, drug barcodes and decision support systems have been proven effective, the use of these information tools may also generate new errors, which must not be disregarded (Anderson & Abrahamson, ; Ruano, Villamañán, Pérez, Herrero, & Álvarez‐Sala, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further path analysis showed that hardware might affect nurses and thereby indirectly influence the medication safety behaviour of nurses. The study found that information technology might reduce errors; although electronic medical records, electronic prescriptions, drug barcodes and decision support systems have been proven effective, the use of these information tools may also generate new errors, which must not be disregarded (Anderson & Abrahamson, ; Ruano, Villamañán, Pérez, Herrero, & Álvarez‐Sala, ).…”
Section: Discussionmentioning
confidence: 99%
“…These differences in overall satisfaction with CPOE among healthcare professionals may be due to diverse causes,5 15–17 23 24 but doubtlessly each one uses the system differently during their daily tasks and their needs are probably different as well. Indeed, not having a virtual system in our hospital to record medication administration parallel to the CPOE system may have caused lower satisfaction with the CPOE in the NP 6. This does not invalidate the obtaining of a single model to record healthcare professionals’ satisfaction, which in subsequent analysis may be stratified to determine satisfaction in both groups and how different factors or confounding variables may influence satisfaction in these groups 21…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of the (now retired) AAP Policy Statement "Prevention of Medication Errors in the Pediatric Inpatient Setting," 71 it has become more apparent that CPOE systems require robust decision support to be safe and effective. 18,[72][73][74][75][76] Some decisionsupport rules for drug and dosing schedules and CPOE systems are now commercially available for children; however, most of them are still created locally. Order sets, reminders, and evidence-based clinical practice guidelines embedded within information systems increase adherence to best practices.…”
Section: Role Of Information Technologymentioning
confidence: 99%